Design, synthesis and molecular modeling studies on novel moxifloxacin derivatives as potential antibacterial and antituberculosis agents - TÜRE, ASLI; KÜÇÜKGÜZEL, İLKAY; KULABAŞ, NECLA (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2019)
Twenty-one novel alkyl/acyl/sulfonyl substituted fluoroquinolone derivatives were designed, synthesized and evaluated for their anti-tuberculosis and antibacterial activity. The targeted compounds were synthesized by the introduction of alkyl, acyl or sulfonyl moieties to the basic secondary amine moiety of moxifloxacin. Structures of the compounds were enlightened by FT-IR, H-1 NMR, C-13 NMR and HRMS data besides elemental analysis. Compounds were initially tested in vitro for their anti-mycobacterial activity against Mycobacterium tuberculosis H37Rv using microplate alamar blue assay. Minimal inhibitory concentration (MIC) values of all compounds were found between > 25.00-0.39 mu g/mL while compounds 1, 2 and 13 revealed an outstanding activity against M. tuberculosis H37Rv with MIC values of 0.39 mu g/mL. Activities of compounds 1-21 against to a number of Gram-positive and Gram-negative bacteria and fast growing mycobacterium strain were also investigated by agar well diffusion and microdilution methods. According to antimicrobial activity results, compound 13 was found the most potent derivative with a IC50 value of < 1.23 mu g/mL against Staphylococcus aureus and clinical strain of methicillin-resistant clinical strain of S. aureus.
Keywords: Fluoroquinolones; Moxifloxacin; Antibacterial activity; Anti-tuberculosis activity; DNA supercoiling assay; Molecular docking; Resistant strains; BIOLOGICAL EVALUATION; CIPROFLOXACIN DERIVATIVES; TOPOISOMERASE-I; DNA GYRASE; HYBRIDS; FLUOROQUINOLONES; ANTICANCER; INHIBITORS; QUINOLONE; COMPLEXES